Falls from height a guide to rescue planning - McCurley, Loui, 1965- (Hoboken, N.J. : Wiley, 2013)
"Occupational fall protection has grown substantially as a safety practice over the past two decades. This book guides the reader in creating a comprehensive plan for post-fall rescue and retrieval in the workplace. Chapters lay out, step by step, a valuable roadmap to follow in developing specific plans for effecting prompt rescue at work locations. This essential book for safety managers and planners aids the employer in making informed decisions in advance about the who, what, when, and how of emergency rescue in the critical first moments following an accidental fall"--
Machine generated contents note: SECTION 1 REGULATORY CONSIDERATIONS, RESCUE PLANS, AND DEVELOPING A RESCUE CAPABILITY CHAPTER 1 The Reason for Rescue CHAPTER 2 Developing a Post Fall Rescue Plan CHAPTER 3 Program Development and Incident Management SECTION 2 EQUIPMENT, SYSTEMS AND SKILLS CHAPTER 4 Equipment for Co-Worker Responders CHAPTER 5 Rescue Equipment and Systems CHAPTER 6 Personal Skills for Rescuers SECTION 3 - PUTTING IT ALL TOGETHER CHAPTER 7 Principles of Rigging CHAPTER 8 Single-Rescuer Techniques CHAPTER 9 Group-Rescue Methods SECTION 4 - SUCCESSFUL WORKPLACE PLANNING CHAPTER 10 Industry Specific Considerations CHAPTER 11 Practical Workplace Application Your Step-by-Step Guide to Developing a CoWorker Assisted Rescue Plan.
Includes index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Industrial safety; Falls (Accidents) -- Prevention; Rescue work; Electronic books